Quantum Stirling Engine with Multiple States in One Dimensional Potential Well - Nailul Hasan (Future Science)
The quantum analogy for of ideal Stirling engine in one dimensional potential well has been explored. It contains single particles with multiple quantum states which is a superposition of many states. The volume in the classical engine is replaced by the length or width of the well. As in the classical one, the quantum Stirling engine consists of two isothermal processes and two isobaric processes. In the analogy of isobaric processes is constant width. The isothermal processes in the quantum engine here are defined by the constant internal energy of particles. Energy conservation is used to calculate the efficiency and work in each process. We found that the efficiency of the quantum Stirling engine has similarities with the classical Stirling engine.